Epidemiological profile of patients with systemic lupus erythematosus in the city of Vitória - Espírito Santo - Soares, Yuri Venancio; Guerrieri, Caroline Gastaldi; Pancoto, João Alexandre Trés (Brazilian Journal of Production Engineering, 2023)
Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease characterized by periods of remission and relapse. Patients with SLE suffer from a chronic disease course burdened with multi-organ comorbidities. Epidemiological studies on SLE are very scarce in Brazil, mainly in the state of Espírito Santo. In view of this scarcity of epidemiological data, the present study carried out an epidemiological research in patients with SLE, characterizing the causes of mortality in the municipality of Vitória between 2009 and 2019, using the DATASUS database. According to the analysis of deaths of patients with SLE that occurred in Vitória (n=269), the main underlying causes of death were diseases of the musculoskeletal system and connective tissue, infectious and parasitic diseases, diseases of the respiratory system, diseases of the circulatory system and diseases of the genitourinary system, which together represented 84.39% of death records. The female sex had a higher number of deaths compared to men, the results were significant for women of brown and white ethnicity, aged between 10-49 years, in addition, this age group had the highest number of deaths in Vitória. Of the 269 deaths recorded, 182 are of patients who do not live in Vitória, which shows that many cities in Espírito Santo still do not have specialists for this type of care and there is a lack of more complex health services to assist them in cities in the interior of Espírito Santo.